AB0537 Usability of an innovative and interactive electronic system for collection of patient-reported data in axial spondyloarthritis: comparison with the traditional paper-administered format. (23rd January 2014) - Salaffi, F.; Gasparini, S.; Ciapetti, A.; Gutierrez, M.; Carotti, M.; Grassi, W.
Abstract : Objectives: To evaluate the validity, in terms of the patients' acceptance, preference, feasibility, and reliability of an innovative, interactive computerized system for collection of patient-reported outcome (PRO) data on axial spondyloarthritis (axial-SpA) against the paper-and-pencil version. Methods: Fifty five patients with axial-SpA completed both the touch-screen and the paper-administered set of questionnaires. A computerized touch-screen system, namely SPEAMonitor, was developed to capture PRO data. Variables recorded include demographic data, patient's assessment of general health status, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath AS Metrology Index (BASMI)and acute phase reactants levels. In order to assess the patient's acceptance, preference, and the feasibility of computer-based questionnaires, the participants filled in an additional questionnaire. Time taken to complete both formats was measured. In a further test-retest study, 25 patients were evaluated. Results: The agreement between the paper-administered and computer touch-screen format of the BASFI, BASDAI questionnaires and the ASDAS scores was excellent. Intraclass correlation coefficients (ICC) between data ranged from 0.90 to 0.96. Additionally, the test-retest study showed a very good agreement between the scores for the two administrations (ICC ≥0.90). Age, computer experience, or educational level had no significant impact on the results. The computerized questionnaires were reported to be easier to use. Mean time spent completing the questionnaires on touch-screen was 5.1 min and on paper 7.9 min. Conclusions: Our newly developed computer-assisted touch-screen questionnaires for PRO in axial-SpA were well accepted by patients, with good data quality, reliability, and score agreement. Acknowledgements: The study was sponsored by an unrestricted educational grant from AbbVie S.r.l. - Abbott Italia. AbbVie played no role in the study design or in the collection, analysis, or interpretation of the data, the writing of the manuscript, or in the decision to submit the manuscript for publication. Disclosure of Interest: F. Salaffi Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, Abbott Immunology, Wyeth Lederle and Pfizer, S. Gasparini: None Declared, A. Ciapetti Speakers bureau: Bristol-Myers Squibb, M. Gutierrez Speakers bureau: Abbott Immunology, UCB Pharma, Esaote, and Bristol-Myers Squibb., M. Carotti: None Declared, W. Grassi Grant/research support from: Bristol-Myers Squibb and Abbott Immunology, Speakers bureau: Bristol-Myers Squibb, Abbott Immunology and Pfizer